2017
DOI: 10.1002/ijgo.12140
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and its determinants among women infected with HIV

Abstract: FSD was prevalent among women with HIV infection. Care providers need to routinely address FSD as part of a comprehensive care package in the study setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 26 publications
3
32
6
Order By: Relevance
“…3 A systematic review reported a prevalence of sexual dysfunction ranging from 32% to 61% among females living with HIV. 21 On the other hand, our findings are lower than the three studies conducted in Nigeria where the reported prevalences were 95% among women of reproductive, 22 89.2% among women living with HIV 6 and 53.3% among female students respectively. 23 The proportion found in our study is also lower than the 88% reported among diabetic women in Nigeria 5 and the 79.2% found among Chinese women with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…3 A systematic review reported a prevalence of sexual dysfunction ranging from 32% to 61% among females living with HIV. 21 On the other hand, our findings are lower than the three studies conducted in Nigeria where the reported prevalences were 95% among women of reproductive, 22 89.2% among women living with HIV 6 and 53.3% among female students respectively. 23 The proportion found in our study is also lower than the 88% reported among diabetic women in Nigeria 5 and the 79.2% found among Chinese women with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 86%
“…4,5 Among women, sexual disorders are characterized by subjective reports of difficulties or limitations in the sexual domains affected. 6 Women with chronic diseases such as human immunodeficiency virus (HIV) have been reported to experience sexual dysfunction related to sexual desire, arousal, orgasm, and dyspareunia. 7 Among the tools for screening for FSD, the Female Sexual Function Index (FSFI) is widely used and has criteria for each area of dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies among gay and bisexual men living with HIV found that as many as 70% of reported problems with sex in the first year after diagnosis (Bourne et al, 2012;Huntingdon et al, 2020;Sandfort et al, 2013). Among women living with HIV, sexual problems were also found to be highly prevalent (Agaba et al, 2017;Bell et al, 2006). The most commonly reported sexual health problem among men who have sex with men (MSM) living with HIV is loss of libido, followed by erectile dysfunction (Bourne et al, 2012;Santi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%